A Tumultuous Course of Exogenous Testosterone by a Bodybuilder Causing a Catastrophic Hypercoagulable State in the Surgical Intensive Care Unit - Kevin Lee; Sophia Toraby; Robert Cotterman; Babatunde Oriowo; John Fish (Case Reports in Vascular Medicine)
Present literature demonstrates an equivocal relationship between testosterone and thrombogenicity. Herein, we describe a case in which a patient used an unspecified amount and duration of exogenous testosterone injections, subsequently developing thrombotic events in his: right radial artery, right iliac artery, superficial femoral artery, splenic artery and a bilateral lower lobe pulmonary embolism. As a result, clinicians should consider exogenous testosterone use as a potential risk factor when the etiology of a patient’s thrombotic events are not clear. We also completed a literature review of the molecular mechanisms in which testosterone can increase the clot burden through an increases human platelet thromboxane A2 receptor density and an increase in erythropoiesis.